2020
DOI: 10.1200/jco.2020.38.15_suppl.4050
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic effect of specific RAS/BRAF mutations in patients (pts) with metastatic colorectal cancer (mCRC).

Abstract: 4050 Background: Somatic mutations in KRAS, HRAS, NRAS (extended RAS) and BRAF have prognostic and predictive impact in pts with mCRC. We analyzed the prognostic impact of specific somatic mutations in extended RAS and BRAF. Methods: We retrospectively reviewed the electronic medical records of pts with mCRC at our institution who underwent comprehensive genomic profiling (CGP) utilizing the Foundation One assay. DNA was extracted from clinical specimens and CGP was performed on hybrid-capture, adaptor ligati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Indeed, looking at other prognostic factors that might have lessened the impact of KRAS G12C mutation both on PFS and OS, it can be observed that the cohort of our study is well balanced for all stratification factors that are usually considered when assessing survival outcomes. Other studies have not performed the same: George et al (20), for example, have reported that KRAS G12C mutations might be associated with statistically significant differences in OS. Differently from our study, those authors did not report any kind of matching for other relevant prognostic factors (ECOG PS, tumor sidedness, surgery of metastatic sites with radical intent, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, looking at other prognostic factors that might have lessened the impact of KRAS G12C mutation both on PFS and OS, it can be observed that the cohort of our study is well balanced for all stratification factors that are usually considered when assessing survival outcomes. Other studies have not performed the same: George et al (20), for example, have reported that KRAS G12C mutations might be associated with statistically significant differences in OS. Differently from our study, those authors did not report any kind of matching for other relevant prognostic factors (ECOG PS, tumor sidedness, surgery of metastatic sites with radical intent, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have not performed the same: George et al. ( 20 ), for example, have reported that KRAS G12C mutations might be associated with statistically significant differences in OS. Differently from our study, those authors did not report any kind of matching for other relevant prognostic factors (ECOG PS, tumor sidedness, surgery of metastatic sites with radical intent, etc.…”
Section: Discussionmentioning
confidence: 99%
“…More than two MSI were identified as MSI-H, one MSI locus was identified as low-grade microsatellite instability (MSI-L), and no MSI was identified as MSS. Although most microsatellites are located in non-coding regions, misplaced mutations can lead to frameshift mutations, causing tumor-related gene abnormalities, which in turn induce the development of cancer [25][26][27].…”
Section: Microsatellite Instability (Msi) and Mismatch Repair (Mmr) I...mentioning
confidence: 99%